Persepsi Pengunjung Mengenai Kenyamanan Termal di Masjid Agung Istiqamah Tapaktuan - Hisbul Watan; Sri Nengsih; Zia Faizurrahmany El Faridy (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2024)
This researchaims to understand visitors' perceptions of thermal comfort in the Masjid Agung Istiqamah, Tapaktuan. The focus of this research is the aspect of thermal comfort within the mosque, encompassing temperature, humidity, and wind speed, which are measured using a thermohygrometer and an anemometer. Using mixed methods, the study records visitors' responses through observations and qualitative interviews, while quantitative data are obtained from measurements to determine the levels of temperature, humidity, and wind speed in the mosque. A decline in the number of visits to the Agung Istiqamah Mosque in Tapaktuan prompted this research.